ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP KONDISI KESULITAN KEUANGAN BANK DI INDONESIA (Pendekatan Menggunakan Metode Regresi Logistik) - Kartikajati, Evita; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2014)
Bank is a financial intermediary institutions (financial intermediaries) that channel funds from the excess funds (surplus units) to those who need funds (deficit units) at the specified time. This study aimed to analyze the effect of CAR, ROA, Asset Growth, LDR, NPL, and BOPO to the financial distress of bank. The population in this study is Indonesian Banking Company that operates and participate in the rating of banks conducted by Infobank magazine in 2010- 2012, and published in June of each year from 2011 to 2013. Variables used in this study are CAR, ROA, Asset Growth, LDR, NPL, and BOPO. Tool is regression analysis used logistic regression. The multivariate result of this research shows that LDR variable is significantly affect for the financial distress of bank in Indonesia at Î± = 5% in spite of having different sign with that being predicted. Asset Growth variable have the same sign as that being predicted and significant. CAR and ROA variables are not significant and have the same sign with that being predicted. NPL and BOPO variables are significantly affect for the financial distress of bank in Indonesia at Î± = 10% have the same sign with that being predicted. Generally, the result were not accept all Ha. The accuracy of prediction bank fragility reaches to 98,2%.